Effect of the plant growth stimulant zeatin on regeneration capacity of some Physalis species in vitro culture - Yaroshko, O.; Rakhmetov, D.; Kuchuk, M. V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2020)
The aim of the study was to find an efficient culture medium for regeneration of Physalis species in vitro to provide their further propagation ex vitro and obtain fructiferous plants from the regenerants. Physalis peruviana L., P. ixocarpa Broth. (cv. Likhtaryk), and P. pubescens L. (cv. Zarynka) were taken as plant material for the research. Plant introduction into culture and regenerant production were carried out in vitro; the rooting of mature plants and obtaining plants with ripe fruits took place in a greenhouse and in open ground (ex vitro). To obtain regenerants, we used Murashige and Skoog (MC30) medium supplemented with the growth stimulant zeatin (Zea) at a concentration of 0.5–3 mg/l. The growth stimulant 6-benzylaminopurine (BAP) was used to elongate the regenerant stalks, and the growth stimulator α-naphthylacetic acid (NAA) was used to initiate root formation. Plant regeneration frequency and the number of regenerants per explant served as indicators of the efficiency of various zeatin concentrations on the physalis regenerative capacity. The most effective media for the shoot regeneration from cotyledonous leaf explants were MC30 + 1 mg/l Zea and MC30 + 2 mg/l Zea. Regeneration frequency on these media was 46.15 % and 53.84 % for P. ixocarpa (cv. Likhtaryk), 38.46 % and 45 % for P. peruviana, and 27 % and 34 % for P. pubescens (cv. Zarynka) respectively. The emerged regenerants were separated from explants and transferred to MC30 medium supplemented with 1 mg/l of BAP + 0.1 mg/l of NAA for stalk growth and rooting. After a month of cultivation, juvenile plants were obtained. They were transferred to a greenhouse for adaptation, and later to open ground at the experimental plot. Three months after the regenerant emergence, we obtained fertile plants, which bloomed and bore fruit. The regenerants for domestic varieties of P. ixocarpa (cv. Likhtaryk) and P. pubescens (cv. Zarynka) were obtained for the first time. We established a direct relationship between the concentration of zeatin and both the frequency of plant regeneration and the number of regenerants per explant.